The Effect Of Accounting Conservatism, Profit Management, Capital Intensity, And Thin Capitalization On Tax Avoidance - Rifani, Labibah Ayudita; Subandi, Hendi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Tax avoidance is an effort made by the company to reduce the amount of tax payable by legal means. This study aims to examine the effect of factors in accounting conservatism, earnings management, capital intensity, and thin capitalization on tax avoidance. The study used 110 samples from primary consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2018-2022, based on purposive sampling. The results of this study indicate that accounting conservatism and earnings management have a positive influence on tax avoidance. Meanwhile, capital intensity harms tax avoidance, while thin capitalization does not. This study has implications for various parties, including the regulator. The results indicate that tax regulations need to be strengthened to minimize opportunities or loopholes in regulatory weaknesses exploited by companies to conduct tax avoidance.